Los procesos de cambio organizacional y la generación de valor (2014)
The purpose of this paper is to explore, based on conceptual considerations and a literature review, some of the elements inherent to the generation of organizational changes as part of the management in search of value creation. There are many assumptions made about change, and organizations often make decisions based on misconceptions about what it really means, and on how to understand and face the need to make decisions when required, plus the consequences of acting ad hoc in that direction. Organizational changemanagement hasmany facets thatmust be understood before starting, particularly if management wants to respond appropriately to the needs of understanding it and using it to create value in organizations.